Kajian Semantik atas Konsep Hablun dalam Al-Quran - Farhan Ahsan Anshari (Jurnal Iman dan Spiritualitas, 2021)
In general, people interpret a rope as a tool for binding. In the extensive Indonesian dictionary, rope means goods with long threads, made of various materials (coconut fiber, palm fiber, plastic, etc.) used for binding, pulling. Whereas in Arabic and the Quran, rope mean hablun, and it does not always mean rope. In the interpretation of hablun it is known as al-jama'ah, agreement, the Quran, Islam, necklaces of commands and prohibitions, neck veins. Whereas the word rope is only a tool for binding, pulling, pulling, tightening, etc. The theory used in this research is semantics. Semantics is a science that is used to explore or study a meaning in words. The semantics used is the encyclopedic model introduced by Dadang Darmawan and Irma Riyani in their journal article, which refutes the Izutsu semantic model with several shortcomings. The word hablun has a primary meaning in the form of a long tool used to bind. In contrast, in relational meaning, it means abstract in jahiliyah poetry and mass media, while in interpretation, it means concrete in Makkiyah letters and abstract meaning in madaniyah surahs. The concept of the word hablun is fundamental to learn because it is a rope and has important lessons for the safety of the world and the hereafter. Among them is that the concept of hablun commands to hold on to the Prophet Muhammad's two inheritances, avoid division, and understand and practice the concept of Islamic sociology.